College Students' Perceptions of Barriers to Bystander Intervention. Issue 15 (August 2020) - Yule, Kristen; Grych, John
Sexual violence is a major problem on college campuses and is associated with a range of negative health consequences for victims. Teaching students to intervene as prosocial bystanders has become a common element of sexual assault prevention efforts; although these programs have demonstrated positive effects on participants' beliefs and knowledge, their impact on actual behavior is weaker. Understanding the factors that inhibit intervening in risky situations may enhance the effectiveness of bystander programs by identifying material that addresses these barriers. A sample of 281 first-year college students indicated whether they had encountered 10 situations that may present elevated risk of sexual or physical assault since arriving on campus, and if so, whether they had done something to intervene. If they had not intervened, they were asked to identify the barriers that had inhibited them. Participants also completed measures of two factors proposed to predict bystander behavior, self-efficacy and emotion regulation. A majority of participants intervened in most of the situations, but only 27% of participants intervened in every situation they encountered. Men and women differed in the barriers they identified most frequently across situations, with men endorsing Perceived Responsibility more often than women, and women reporting Skill Deficits more often than men. Neither men nor women perceived Audience Inhibition to be a significant barrier; it was salient in only one of the 10 situations. Students higher in global bystander self-efficacy were more likely to intervene and less likely to report barriers related to skill deficits and perceived responsibility. These results suggest that existing bystander intervention programs efforts can be improved by fostering a greater sense of collective responsibility in students and teaching specific intervention behaviors.